Ответы и объяснения

2014-01-09T13:25:25+00:00
(2sinx-1)( \sqrt{-cosx}+1)=0
 2sinx-1=0                                                                  \sqrt{-cosx}+1=0
2sinx=1                                                                      \sqrt{-cosx}=-1
sinx=1/2                                                                   -cosx=1
x= (-1)^{n}+ \frac{ \pi }{6} + \pi n,n принадлежит Z       cosx=-1
                                                                                 x= \pi +2 \pi n,n принадлежит Z
ответ x= (-1)^{n}+ \frac{ \pi }{6} + \pi n,n принадлежит Z;   x= \pi +2 \pi n,n принадлежит Z